Intellectual Capital Efficiency Management Effect on Cost of Equity Capital - Victor Fegor Origho; Prince Famous Izedonmi (Journal of Accounting, Finance, and FinTech Advancements, 2025)
This study looked at how managing intellectual capital affects the cost of equity capital in conglomerate firms in Nigeria that are listed on the stock exchange. It used a detailed dataset from 2013 to 2022. Following the Modigliani and Miller theoretical framework, the research explored how human capital efficiency and capital employed efficiency influence the cost of equity capital. To meet the goals of the study, an ex-post facto research design was chosen for its cost-effectiveness and the reliability of historical data in evaluating past events. The developed hypotheses were tested using a random effect regression analysis method, which helps reduce biases and improve the strength and trustworthiness of the findings. The results suggest that the efficiency of human capital does not have a notable impact on the cost of equity capital, whereas the efficiency of capital employed shows a significant negative effect on equity costs. The result underscores the importance of optimizing capital utilization within Nigeria's conglomerate sector. In line with these findings, the study suggests strategic measures to improve capital efficiency, including policies to promote effective capital management and incentives to support resource optimization practices. Additionally, based on the limited impact of human capital investments on reducing equity costs, this study recommends that managers of listed conglomerate firms in Nigeria should not prioritize such investments solely to fix equity costs.